Community Humanitarianism and Social Resilience: Study of YSID within the Framework of Bottom-Up Humanitarianism - Iskandar, Adryan Firmando; Diah Pitaloka; Pratama, Muhammad Abiel Dewa (Department of International Relations, Universitas Brawijaya, 2025)
This article explores the practices of the Yayasan Sanggar Inovasi Desa (YSID) as a concrete example of bottom-up humanitarianism rooted in community participation. Moving beyond the dominant understanding of humanitarian action as short-term crisis response, the study situates YSID’s initiatives within the bottom-up humanitarianism and humanitarian-development nexus, highlighting their transformative and preventive dimensions. Through qualitative analysis of programmes such as Kongres Pemberdayaan Desa, Sistem Informasi Desa (SID), and inclusive economic empowerment, this research demonstrates how participatory governance, knowledge co-production, and institutional resilience collectively foster social dignity and local capacity. Integrating frameworks of human security, the capability approach, and co-production of knowledge, the study identifies three core indicators—participatory governance, institutional resilience, and social ownership—that reflect the effectiveness of YSID’s model. Field findings show that YSID's bottom-up approach avoids elite capture, empowers marginalised groups, and strengthens village institutions. Ultimately, the study argues that humanitarianism can emerge from community development practices that are inclusive, sustainable, and grounded in local values, challenging conventional, top-down humanitarian regimes. The YSID model thus offers a replicable framework for localised humanitarian action in the Global South.